Memory images: Holocaust memory in Balkan cinema(s) - Daković, Nevena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The aim of this paper is to analyse the shift of the representational and narrative paradigms of Holocaust memory in the Balkan films that belong to two genres – of melodrama and historicalfiction. The hybrid format positons the Holocaust (hi)stories – already caught between forgetting and remembrance – on the unstable ground between trauma and nostalgia; between history and memory; or facts and fiction. The “regained visibility of the Holocaust grant us access” to Balkan past and present and oblige us to investigate the convergence of the history and the memory into Holocaust master narrative of the Holocaust. “Bringing the dark past to light” in cinema has manifold effect. First, the Balkan wave of Holocaustfilms, with its mixed generic performances, offers new answers to the traditional issues of, both, the ethics of memory and the ethics of representation. Second, the analysis of five films reveals that the trauma from the past – resisting the closure – has the potential to powerfully resonate in the present day political crises. Re-dressing the trauma of the past, the films present the future violence while fulfilling “the Holocaust dictum ‘never forget’”. Eventually, new representational paradigm gives consistency to the Balkan (hi)stories of the past and coherence to the identity in the present.